CAN A PROPER STRATEGIC PLANNING SECURE ITS IMPLEMENTATION? A CASE IN NEW DISTRICT IN DEVELOPING COUNTRY - Firda Hidayati (Magister Ilmu Administrasi Publik, 2020)
Strategic planning is highly recommended as one of the key factors that determine the success of the organization. However, only a few organizations succeed in implemented it. The research studied causes of poor strategy implementation. The study used Data collection techniques included previous research on factors that influence strategy implementation failures, and a survey of . three levels of managers in 38 agencies in the government. Using structural Equation Modelling-Partial Least Squares (SEM-PLS) as an analysis tool, results showed that stakeholder uncertainty, resources, and expertise are the major factors that influence the failure of strategy implementation. The finding provides an important explanation for poor strategy implementation performance in Batu Bara , which is a new district in Indonesia. One of the key policy recommendations is for the government to take measures toward enhancing the capacity of managers to manage stakeholders’ uncertainty.